CO-BED: Information-Theoretic Contextual Optimization via Bayesian Experimental Design - Ivanova, Desi R.; Jennings, Joel; Rainforth, Tom; Zhang, Cheng; Foster, Adam (ICML 2023, 2023)
We formalize the problem of contextual optimization through the lens of Bayesian experimental design and propose CO-BED – a general, model-agnostic framework for designing contextual experiments using information-theoretic principles. After formulating a suitable information-based objective, we employ black-box variational methods to simultaneously estimate it and optimize the designs in a single stochastic gradient scheme. We further introduce a relaxation scheme to allow discrete actions to be accommodated. As a result, CO-BED provides a general and automated solution to a wide range of contextual optimization problems. We illustrate its effectiveness in a number of experiments, where CO-BED demonstrates competitive performance even when compared to bespoke, model-specific alternatives.